2018
DOI: 10.1371/journal.pone.0196918
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights on the efficient catalysis of hydroperoxide reduction by Ohr: Crystallographic and molecular dynamics approaches

Abstract: Organic hydroperoxide resistance (Ohr) enzymes are highly efficient Cys-based peroxidases that play central roles in bacterial response to fatty acid hydroperoxides and peroxynitrite, two oxidants that are generated during host-pathogen interactions. In the active site of Ohr proteins, the conserved Arg (Arg19 in Ohr from Xylella fastidiosa) and Glu (Glu51 in Ohr from Xylella fastidiosa) residues, among other factors, are involved in the extremely high reactivity of the peroxidatic Cys (Cp) toward hydroperoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…In particular, polar interactions among these three residues are important to stabilize a “closed” conformation of the reduced protein and to activate the thiolate for the reduction of hydroperoxides. Oxidation to the intramolecular disulfide form triggers changes in the interactions of the conserved Glu and in the dynamics of the conserved Arg which favor the “open” conformation which is thought to facilitate reduction. , …”
Section: Cysteine-based Peroxidasesmentioning
confidence: 93%
See 1 more Smart Citation
“…In particular, polar interactions among these three residues are important to stabilize a “closed” conformation of the reduced protein and to activate the thiolate for the reduction of hydroperoxides. Oxidation to the intramolecular disulfide form triggers changes in the interactions of the conserved Glu and in the dynamics of the conserved Arg which favor the “open” conformation which is thought to facilitate reduction. , …”
Section: Cysteine-based Peroxidasesmentioning
confidence: 93%
“…Oxidation to the intramolecular disulfide form triggers changes in the interactions of the conserved Glu and in the dynamics of the conserved Arg which favor the "open" conformation which is thought to facilitate reduction. 303,311 Other proteins with thiols highly reactive toward hydroperoxides include the bacterial transcription factors OxyR and OhrR that control bacterial transcriptional responses to hydrogen peroxide (rate constant of ∼10 5 M −1 s −1 ) 312,313 and organic hydroperoxides, respectively, 312,314,315 and glyceraldehyde 3-phosphate dehydrogenase (GAPDH), a glycolytic pathway enzyme that has been recently proposed to be involved in DNA repair and heme binding and delivery to target proteins, among other functions, 316,317 that reacts with H 2 O 2 with rate constant in the 10 2 −10 3 M −1 s −1 range. 318 An important case of protein inactivation due to Cys oxidation by hydroperoxides are the protein tyrosine phosphatases (PTP), enzymes that catalyze the hydrolysis of phosphotyrosine from specific signal-transducing proteins.…”
Section: Other Examples Of Protein Thiols Prone To Oxidation By Hydro...mentioning
confidence: 99%
“…The fact that PbPrx1 can decompose organic hydroperoxides more efficiently than hydrogen peroxide is not an exclusive characteristic of PbPrx1. Other thiol peroxidases, such as the human PrxV, E. coli thiol peroxidase (EcTpx), and the organic hydroperoxide resistance protein (Ohr) from Xylella fastidiosa are 100–1000-fold more reactive with organic peroxides, as a consequence of a hydrophobic active site microenvironment, which enables interactions with hydrophobic oxidizing substrates (Cussiol et al, 2003 ; Perkins et al, 2014 ; Alegria et al, 2017 ; Piccirillo et al, 2018 ). In this context, our data suggest that the active site microenvironment of PbPrx1 is also highly hydrophobic, suggesting that PbPrx1 may act as a strong scavenger of organic peroxides in P. brasiliensis cells.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the wild-type (WT) parent strain A. baumannii ATCC19606, mutations located in plasmid (pMAC)-derived ohrB were identified both in 3M and 5M strains, resulting in the conversion of arginine at the position 15 (Arg15) to His or Cys of OhrB (Table 2). indicated that the corresponding Arg19 in Ohr from Xylella fastidiosa contributed to the stabilization of XfOhr in the closed state, suggesting that the mutations in 3M and 5M probably affect the function of OhrB [13].…”
Section: Ohrb Mutations Confer Resistance To 6d1mentioning
confidence: 99%